2007
DOI: 10.1162/jocn.2007.19.10.1706
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Time: Impaired Temporal Perception of Multisecond Intervals in Unilateral Neglect

Abstract: Recent neuroimaging and neuropsychological studies have suggested that the right hemisphere, particularly frontal regions, is important for the perception of the passage of time. We examined the ability to estimate durations of up to 60 sec in a group of eight patients with unilateral neglect. When estimating multisecond intervals, neglect patients grossly underestimated all durations. On average, healthy controls (HC) demonstrated reasonably accurate estimates of all durations tested. Although the right hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 70 publications
(130 reference statements)
7
73
0
Order By: Relevance
“…In addition, using f MRI has revealed that the parietal cortex, which acts as an interface between sensory and motor processes, is involved in translating temporal information into action . Finally, evidence for the role of the parietal cortex-the right hemisphere-in the estimation of long intervals was also obtained with patients with unilateral neglect (Danckert et al, 2007), whereas N'Diaye, Ragot, Garnero, and Pouthas (2004) reported that there is a potential contribution for both frontal and parietal cortices.…”
Section: Cerebellummentioning
confidence: 95%
“…In addition, using f MRI has revealed that the parietal cortex, which acts as an interface between sensory and motor processes, is involved in translating temporal information into action . Finally, evidence for the role of the parietal cortex-the right hemisphere-in the estimation of long intervals was also obtained with patients with unilateral neglect (Danckert et al, 2007), whereas N'Diaye, Ragot, Garnero, and Pouthas (2004) reported that there is a potential contribution for both frontal and parietal cortices.…”
Section: Cerebellummentioning
confidence: 95%
“…A further issue worthy of investigation could be to find out whether the perception of the duration of auditory and tactile stimuli is prone to crossmodal distortion effects, analogous to what has been found between auditory and visual stimuli (e.g., Chen & Yeh, 2009;van Wassenhove et al, 2008). Moreover, the potential implementation of the experimental findings in the clinical field, such as in sensory substitution (e.g., Minagawa, Ohnishi, & Sugie, 1996), in the diagnosis (e.g., Danckert et al, 2007;Davalos, Kisley, & Ross, 2002;Gilden & Marusich, 2009;Smith, Harper, Gittings, & Abernethy, 2007), or in the treatment (Powers, Hillock, & Wallace, 2009;Thaut, 2005;Vargas & Yu, 2008) of psychiatric and neurological diseases, would be an interesting issue to be investigated in future studies.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 98%
“…Our data indicate that such processes can also be associated with symbolic numbers, in line with lesion data showing that right TPJ lesions affect attention-related processes. These processes, albeit not always in the context of TPJ lesions, are known to interfere with number ( Vuilleumier, Ortigue, & Brugger, 2004) or with continuous quantity manipulation (Danckert et al, 2007).…”
Section: One or Multiple Quantity Systems?mentioning
confidence: 99%